A method for preparing a plastic optical fiber composite scintillator

By adding ZnO nanoparticles to the plastic scintillator and setting up optical fiber structures, the problems of low light yield and conduction efficiency of existing plastic scintillators are solved, and higher light yield and more efficient photon conduction are achieved, which improves the sensitivity of the detector.

CN116728811BActive Publication Date: 2025-04-04鄂尔多斯市国源矿业开发有限责任公司 +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310704201.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-14
Publication Date
2025-04-04
Estimated Expiration
2043-06-14

AI Technical Summary

Technical Problem

The light yield of existing plastic scintillators is low and the photon conduction efficiency is not high, resulting in limited application of detectors in narrow spaces.

Method used

Add alumina-number ZnO nanoparticles as ray capture material and auxiliary scintillator to traditional polystyrene plastic scintillators, and optical fiber-like structures are installed inside them to improve light yield and conduction efficiency.

Benefits of technology

By increasing ZnO nanoparticles and fiber-like structures, the light yield of scintillators and the conduction efficiency of photons are improved, the instrument structure is simplified, the photon dissipation loss is reduced, and the sensitivity of the detector is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116728811B_ABST
    Figure CN116728811B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a plastic optical fiber composite scintillator. The method comprises the following steps: dissolving ZnO nanoparticles, 2,5-diphenyloxazole and 1,4-bis(5-phenyl-2-oxazolyl)benzene in styrene in a certain proportion to obtain a B liquid; prepolymerizing the prepared B liquid and pressing it into an optical fiber capillary in a closed container; uniformly heating the B liquid prepolymer in the optical fiber capillary to solidify it, then cutting and stripping the optical fiber of the middle capillary to obtain a B material optical fiber; dissolving 2,5-diphenyloxazole and 1,4-bis(5-phenyl-2-oxazolyl)benzene in styrene in a certain proportion to obtain an A liquid; heating the A liquid for prepolymerization, and then wrapping a pre-suspended B material optical fiber in a closed container to increase polymerization to obtain a final scintillator, thereby improving light yield and light transmission rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a plastic optical fiber composite scintillator. Background Art

[0002] Scintillator is a type of material that can emit light after absorbing high-energy particles or rays. It, together with light collecting components and photoelectric conversion devices, constitutes a radiation detector that is used to detect various high-energy particles and rays. It is widely used in high-energy physics, nuclear physics, radiation medicine, geological exploration, explosion-proof detection and other fields.

[0003] Scintillators used in radiation detectors can be divided into two categories: organic scintillators and inorganic scintillators. Plastic scintillators are solid solutions of organic scintillators in plastics. They belong to organic scintillators and can be used to detect α, β, γ, fast neutrons, protons, cosmic rays and fission fragments. The components of plastic scintillators are usually composed of matrix scintillators and wave shifters. When irradiated by high-energy rays and high-energy particles, they can emit fluorescence of a specific wavelength. They have the advantages of non-deliquescent, stable performance, radiation resistance, short scintillation decay time and low price. They are a widely used scintillator today.

[0004] However, due to the material of plastic scintillators, the current light yield of plastic scintillators is relatively low. Because the atomic number of plastic scintillators is small and their ability to absorb radiation is weak, a large number of high-energy particles that pass through the scintillator have not yet stimulated the scintillator in the scintillator to emit light, and the detector has requirements for the decay count rate of the detected rays, which is manifested in the use of the detector as a requirement for the amount of photons generated. Therefore, in order to capture enough rays and achieve the ideal detection effect, the size of the scintillator is often designed to be very large. Taking a certain gamma-ray method for coal gangue identification equipment for coal mine conditions as an example, the size of the scintillator it uses is 1m*0.2m*0.1m and weighs tens of kilograms, which creates obstacles for detection and use in narrow spaces such as mines, and hinders the application of technologies such as natural ray method coal gangue identification in coal mines and other fields.

[0005] In addition, the photons currently generated by the plastic scintillator need to be transmitted to the photomultiplier tube through optical glass or optical fiber for detection. The collection and transmission path of photons is: scintillator-light-guiding glass-photomultiplier tube. This three-level collection mechanism has two interfaces: scintillator to light-guiding glass, and light-guiding glass to photomultiplier tube. Photons suffer from refraction and absorption losses when crossing the interface, and due to problems with the preparation process, there is inevitably a gap between the two interfaces, resulting in low coupling efficiency of the photon transmission path, affecting detection accuracy. Although there are literature reports that mechanical grooves can be made in the plastic scintillator to place the transmission optical fiber, so as to increase the contact area between the optical fiber and the scintillator and thus improve the coupling efficiency of the light transmission path, this process also has the problem of scratching the contact surface between the plastic scintillator and the optical fiber, and the improvement of light transmission efficiency is not obvious.

[0006] Therefore, how to improve the light yield of plastic scintillators and how to improve the photon transmission efficiency are still urgent issues to be solved. Summary of the invention

[0007] In view of the problems of low light yield and low photon conduction efficiency of current plastic scintillators, the present invention provides a plastic optical fiber composite scintillator and a preparation method thereof. On the basis of the traditional polystyrene plastic scintillator, high atomic number ZnO nanoparticles are added as ray capture materials and auxiliary scintillators to increase light yield; at the same time, there is a fiber-like structure in the internal scintillator area, and the refractive index difference of the materials on both sides of the fiber-like structure makes the photons generated by the rays fully reflected in the light structure, reducing the dispersion of photons inside the scintillator. The specific technical scheme is as follows:

[0008] A method for preparing a plastic optical fiber composite scintillator comprises the following steps:

[0009] 1) Dissolve ZnO nanoparticles, 2,5-diphenyloxazole and 1,4-bis(5-phenyl-2-oxazolyl)benzene in styrene in a certain proportion and mix them evenly to obtain liquid B;

[0010] 2) Prepolymerizing the prepared liquid B in a constant temperature box to obtain liquid B prepolymer;

[0011] 3) Inject the liquid B prepolymer into a sealed container, insert the optical fiber capillary through the sealed container below the liquid surface of the liquid B prepolymer; press the liquid B prepolymer into the optical fiber capillary, and then heat it evenly to solidify the liquid B prepolymer in the optical fiber capillary; then cut and strip the optical fiber of the middle capillary to obtain the B material optical fiber;

[0012] 4) Dissolve 2,5-diphenyloxazole and 1,4-bis(5-phenyl-2-oxazolyl)benzene in styrene in a certain proportion and mix well to obtain liquid A;

[0013] 5) Heat liquid A and keep it warm for a period of time to perform prepolymerization. At the same time, suspend the optical fiber of material B in a closed container, introduce nitrogen to remove the air, and then slowly add the heated liquid A along the inner wall of the closed container;

[0014] 6) After the A liquid is added, slowly raise the temperature in the sealed container to the predetermined temperature, keep it warm for a period of time, and then slowly lower the temperature to room temperature to allow the A liquid to polymerize and solidify to obtain the final scintillator.

[0015] In the aforementioned method for preparing a plastic optical fiber composite scintillator, in step 1), in the B liquid, the mass fraction concentration of ZnO nanoparticles is 8 to 12%, preferably 10%; the mass fraction concentration of 2,5-diphenyloxazole is 0.6 to 1.2%, preferably 1%; and the mass fraction concentration of 1,4-bis(5-phenyl-2-oxazolyl)benzene is 0.01 to 0.03%, preferably 0.02%.

[0016] In the aforementioned method for preparing a plastic optical fiber composite scintillator, in step 2), the temperature at which the B liquid is prepolymerized in a constant temperature box is 55° C., and the prepolymerization time is 120 hours.

[0017] In the aforementioned method for preparing a plastic optical fiber composite scintillator, in step 3), the liquid B prepolymer is pressed into the optical fiber capillary by relying on capillary action and by introducing nitrogen gas at the liquid surface to allow the prepolymer to enter the optical fiber capillary; the uniform heating is performed at 45°C, and the optical fiber capillary is slowly heated from bottom to top to solidify and shrink the liquid B prepolymer therein; the length of the cut B material optical fiber is determined according to the size of the scintillator, which is an integer multiple of the length of the scintillator to be prepared.

[0018] In the aforementioned method for preparing a plastic optical fiber composite scintillator, in step 4), in the liquid A, the mass fraction concentration of 2,5-diphenyloxazole is 0.6-1.2%, preferably 1%; the mass fraction concentration of 1,4-bis(5-phenyl-2-oxazolyl)benzene is 0.01-0.03%, preferably 0.02%.

[0019] In the above-mentioned method for preparing a plastic optical fiber composite scintillator, in step 5), the A liquid is heated to a temperature of 65 to 80° C. and kept warm for 45 to 50 hours; and the speed of adding the A liquid is 100 ml / h.

[0020] In the aforementioned method for preparing a plastic optical fiber composite scintillator, in step 5), the volume ratio of the suspended B material optical fiber to the injected A liquid is 1:7-12.

[0021] In the above-mentioned method for preparing plastic optical fiber composite scintillator, in step 6), the temperature rise and fall procedure after the A liquid is filled is: first, the temperature in the sealed container is raised to 100°C at a rate of 5°C per hour and then maintained for 120 hours, and then the temperature in the sealed container is lowered to room temperature at a rate of 5°C per hour.

[0022] The beneficial effects of the present invention are:

[0023] 1) The present invention divides the traditional polystyrene plastic scintillator into two parts, one of which is added with high atomic number material ZnO nanoparticles as a ray capturing material and auxiliary scintillator, and is made into an optical fiber material, and then the optical fiber material is suspended and solidified in the other part of the polystyrene plastic scintillator, thereby increasing the light yield and the photon transmission efficiency.

[0024] 2) The suspended optical fiber in the scintillator of the present invention not only serves as a flash ray capturing material and assists the scintillator in generating photons, but also, as a built-in optical fiber, can be directly connected to the photomultiplier tube after being concentrated on the side where the scintillator is connected to the photomultiplier tube, thus playing the role of the light-guiding glass in transmitting photons in the traditional process, eliminating the intermediate component of the light-guiding glass and simplifying the instrument structure; and since there is a difference in refractive index between the optical fiber and the polystyrene plastic scintillator, the photons generated by the irradiation of the rays will be collected in the optical fiber and transmitted to the coupled photomultiplier tube, which effectively reduces the photon escape loss and improves the photon transmission efficiency compared to the traditional production process of mechanically grooving and placing the transmission optical fiber.

[0025] 3) The scintillator optical fiber prepared by the method of the present invention has two photon generation pathways: Path 1: PPO is used as the first scintillator to absorb γ-ray radiation energy, and the π electrons of the benzene ring in PPO are excited and then retreat to stimulate fluorescence, and POPOP absorbs the fluorescence excited by PPO, and the fluorescence wavelength moves to the range matching the photomultiplier tube; Path 2: ZnO is used as a high-energy ray capture material to absorb γ-ray radiation energy, and after being irradiated, it emits ultraviolet light of 380 to 400 nm, which is close to the wavelength of light emitted by the traditional PPO scintillator. POPOP absorbs the fluorescence excited by ZnO, and the fluorescence wavelength moves to the range matching the photomultiplier tube; thereby increasing the light generation amount, and compared with the traditional scintillator without adding ZnO, the total light output of the scintillator of the present invention is increased by 9%, which is a significant improvement. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a schematic diagram of the structure of the plastic optical fiber composite scintillator of the present invention;

[0027] Figure 2 This is a diagram of the light yield simulation effect of the scintillator prepared by the method of the present invention in the Geant4 particle transport simulation software. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solution and advantages of the present invention more clear, the technical solution of the present invention will be clearly and completely described below in conjunction with embodiments and drawings.

[0029] Example 1

[0030] This embodiment is a method for preparing a plastic optical fiber composite scintillator, comprising the following steps:

[0031] 1) Dissolve ZnO nanoparticles, 2,5-diphenyloxazole (PPO) and 1,4-bis(5-phenyl-2-oxazolyl)benzene (POPOP) in styrene; wherein the mass fraction concentration of ZnO nanoparticles is 8-12%, the mass fraction concentration of 2,5-diphenyloxazole (PPO) is 0.6-1.2%, and the mass fraction concentration of 1,4-bis(5-phenyl-2-oxazolyl)benzene (POPOP) is 0.01-0.03%, and mix them uniformly by ultrasonic mixing to obtain a transparent B solution.

[0032] 2) Place the prepared liquid B in a constant temperature box, set the temperature to 55°C, and maintain it for 120 hours for prepolymerization to reduce its fluidity and increase its viscosity to obtain liquid B prepolymer.

[0033] 3) Pour liquid B prepolymer into a sealed container, insert the optical fiber capillary through the sealed container and below the liquid surface of the liquid B prepolymer, introduce nitrogen to pressurize it, and press the liquid B prepolymer into the optical fiber capillary by capillary action and nitrogen pressure. Then, uniformly heat the temperature to 110°C to solidify the liquid B prepolymer, then cut the optical fiber in the middle of the capillary and peel it off to obtain the material B optical fiber, whose length is an integer multiple of the scintillator to be prepared.

[0034] 4) 2,5-diphenyloxazole (PPO) and 1,4-bis(5-phenyl-2-oxazolyl)benzene (POPOP) are dissolved in styrene; similarly, the mass fraction concentration of 2,5-diphenyloxazole (PPO) is 0.6-1.2%, and the mass fraction concentration of 1,4-bis(5-phenyl-2-oxazolyl)benzene (POPOP) is 0.01-0.03%, and ultrasonic mixing is performed to obtain a transparent liquid A.

[0035] 5) Heat liquid A to 65-80°C and keep it warm for 45-50 hours for prepolymerization; at the same time, pre-suspend optical fiber B in a closed container, introduce nitrogen to remove the air, and then slowly add heated liquid A along the wall of the closed container; the volume ratio of the suspended optical fiber B to the injected liquid A is 1:7-12.

[0036] 6) After the A liquid is added, the temperature in the sealed container is first raised to 100°C at a rate of 5°C per hour and maintained for 120 hours, and then the temperature in the sealed container is lowered to room temperature at a rate of 5°C per hour to solidify and polymerize into the final scintillator.

[0037] Example 2

[0038] This embodiment adopts the preparation method described in Example 1 to prepare a plastic optical fiber composite scintillator. The specific method is as follows: first, 100g ZnO nanoparticles, 10g PPO and 2g POPOP are dissolved in 1000g styrene, ultrasonically oscillated for 3min to dissolve the components, and then ultrasonically oscillated for 10min to mix the materials evenly to obtain a transparent B liquid. Nitrogen is introduced into the sealed preparation container to remove oxygen to avoid fluorescence quenching caused by oxidation; then the B liquid is placed in a constant temperature box, the temperature is set to 50°C, and the temperature is kept for 120h to obtain a B liquid prepolymer. Subsequently, the B liquid prepolymer is injected into a sealed container, and the optical fiber capillary is inserted through the sealed container under the liquid surface of the B liquid prepolymer, and nitrogen is introduced to pressurize it, and the B liquid prepolymer is pressed into the capillary by capillary action; then, it is uniformly heated to 110°C to solidify the B liquid prepolymer, and then the optical fiber in the middle of the capillary is cut and stripped to obtain a B material optical fiber with a length of 1.8m for standby use.

[0039] Take another 10gPPO and 2gPOPOP and dissolve them in 1000g of styrene. Perform ultrasonic oscillation for 3 minutes to dissolve the components, and then perform ultrasonic oscillation for 10 minutes to mix the materials evenly to obtain a transparent liquid A. Then heat the liquid A to 55°C and keep it warm for 120 hours for prepolymerization. At the same time, pre-suspend the optical fiber of material B in a closed container, and introduce nitrogen to remove the air. Then, slowly add the hot liquid A to the closed container along the wall of the closed container at a rate of 100ml / h. The volume ratio of the suspended optical fiber of material B to the injected liquid A is 1:10. After the injection of liquid A, first increase the temperature in the closed container to 100°C at a rate of 5°C per hour and maintain it for 120 hours to polymerize the liquid A. Then, reduce the temperature in the closed container to room temperature at a rate of 5°C per hour to solidify it. Finally, a plastic optical fiber composite scintillator is obtained. Its size is 0.9m*0.2m*0.1m. Figure 1 The light yield simulation effect in Geant4 particle transport simulation software is shown in Figure 2 shown.

[0040] Example 3

[0041] This example investigates the effect of adding ZnO nanoparticles on the light yield of the prepared plastic optical fiber composite scintillator.

[0042] In this embodiment, there are two types of scintillators used for investigation, one is a plastic optical fiber composite scintillator scintillator (scintillator 1) prepared completely by the method described in Example 2, and the other is a plastic optical fiber composite scintillator (scintillator 2) for comparison without the addition of ZnO nanoparticles. The preparation method of the comparison scintillator is consistent with the preparation method in Example 2 except that ZnO nanoparticles are not added. The size of the prepared scintillators is 0.9m*0.2m*0.1m.

[0043] Scintillators 1 and 2 were connected to photomultiplier tubes respectively, and corresponding gamma-ray gangue identification devices were prepared respectively, and these devices were used to detect the same coal mine location. At the same time, the traditional gamma-ray gangue identification device (1m*0.2m*0.1m) was used as a control.

[0044] The detection effects of different scintillators were investigated by taking whether gangue was detected and the sensitivity of detecting pure coal and pure gangue as indicators. The results are shown in Table 1.

[0045] Table 1. Effect of ZnO nanoparticles on the light yield of the prepared plastic optical fiber composite scintillator

[0046]

[0047] From the results shown in Table 1, it can be seen that the light yield of the optical fiber plastic scintillator with ZnO nanoparticles added is increased by about 4% compared with the plastic scintillator without ZnO nanoparticles added; compared with the scintillator of traditional equipment, not only the volume is significantly reduced, but the detection sensitivity is also increased by 9%, the effect is quite significant.

[0048] Example 4

[0049] This example is to investigate the effect of the volume ratio of the suspended B material optical fiber to the injected A liquid on the light yield of the prepared plastic optical fiber composite scintillator.

[0050] In this embodiment, the volume ratio of the B material optical fiber and the injected A liquid in the scintillator used for investigation is shown in Table 2, and the preparation methods of each scintillator are also consistent with the preparation method of the plastic optical fiber composite scintillator in Example 2. The size of each scintillator is 0.9m*0.2m*0.1m. Each scintillator is connected to a photomultiplier tube, and corresponding gamma-ray method coal gangue identification equipment is prepared respectively, and these equipments are used to detect the same coal mine location.

[0051] Similarly, whether gangue is detected and the sensitivity of detecting pure coal and pure gangue are used as indicators to examine the detection effect of different scintillators. The results are shown in Table 3.

[0052] Table 2. Volume ratio of B material fiber to A liquid in each scintillator

[0053]

[0054] Table 3. Effect of the volume ratio of B material fiber to injected A liquid on the light yield of the prepared plastic fiber composite scintillator

[0055]

[0056] From the results shown in Table 3, it can be seen that when the volume ratio of the suspended B material optical fiber to the injected A liquid is 1:7-12, the prepared plastic scintillator has good transmittance and high light yield. When the volume ratio is 1:10, the overall transmittance and light yield of the plastic scintillator are the highest. When the volume ratio of the B material optical fiber to the injected A liquid is less than or equal to 1:5, the light yield is low and is not conducive to survey. When the volume ratio of the B material optical fiber to the injected A liquid is greater than or equal to 1:15, the transparency of the scintillator will drop sharply, and the detection sensitivity will also drop, which is not suitable for detector use.

[0057] It is obvious to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be regarded as exemplary and non-restrictive from any point of view. In addition, it should be understood that although this specification is described in accordance with the implementation mode, it does not include only one technical solution. This narrative mode of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole, and the technical solutions in the embodiments can also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing a plastic optical fiber composite scintillator, characterized in that: The steps include: 1) Dissolving ZnO nanoparticles, 2,5-diphenyloxazole and 1,4-bis(5-phenyl-2-oxazolyl)benzene in styrene in a certain proportion and mixing them evenly to obtain liquid B; in the liquid B, the mass fraction concentration of ZnO nanoparticles is 8-12%, the mass fraction concentration of 2,5-diphenyloxazole is 0.6-1.2%, and the mass fraction concentration of 1,4-bis(5-phenyl-2-oxazolyl)benzene is 0.01-0.03%; 2) Prepolymerizing the prepared liquid B in a constant temperature box to obtain liquid B prepolymer; 3) Inject the liquid B prepolymer into a sealed container, insert the optical fiber capillary through the sealed container below the liquid surface of the liquid B prepolymer; press the liquid B prepolymer into the optical fiber capillary, and then heat it evenly to solidify the liquid B prepolymer in the optical fiber capillary; then cut and strip the optical fiber of the middle capillary to obtain the B material optical fiber; 4) dissolving 2,5-diphenyloxazole and 1,4-bis(5-phenyl-2-oxazolyl)benzene in styrene in a certain ratio and mixing them evenly to obtain liquid A; in the liquid A, the mass fraction concentration of 2,5-diphenyloxazole is 0.6-1.2%, and the mass fraction concentration of 1,4-bis(5-phenyl-2-oxazolyl)benzene is 0.01-0.03%; 5) Heat and keep liquid A warm for a period of time for prepolymerization, and at the same time, suspend optical fiber B in a closed container, introduce nitrogen to remove air, and then slowly add heated liquid A along the inner wall of the closed container; the volume ratio of the suspended optical fiber B to the injected liquid A is 1:7-12; 6) After the A liquid is added, slowly raise the temperature in the sealed container to the predetermined temperature, keep it warm for a period of time, and then slowly lower the temperature to room temperature to allow the A liquid to polymerize and solidify to obtain the final scintillator.

2. The method for preparing a plastic optical fiber composite scintillator according to claim 1, characterized in that: In the liquid B, the mass fraction concentration of ZnO nanoparticles is 10%, the mass fraction concentration of 2,5-diphenyloxazole is 1%, and the mass fraction concentration of 1,4-bis(5-phenyl-2-oxazolyl)benzene is 0.02%.

3. The method for preparing a plastic optical fiber composite scintillator according to claim 1, characterized in that: In step 2), the temperature of prepolymerization of liquid B in a thermostat is 55° C., and the prepolymerization time is 120 h.

4. The method for preparing a plastic optical fiber composite scintillator according to claim 1, characterized in that: In step 3), The B liquid prepolymer is pressed into the optical fiber capillary by relying on capillary action and by introducing nitrogen gas at the liquid surface so that the prepolymer liquid enters the optical fiber capillary; The uniform heating is to slowly heat the optical fiber capillary from bottom to top to 110° C. so that the liquid B prepolymer inside it solidifies and shrinks. The length of the cut B material optical fiber is determined according to the size of the scintillator and is an integer multiple of the length of the scintillator to be prepared.

5. The method for preparing a plastic optical fiber composite scintillator according to claim 1, characterized in that: In the liquid A, the mass fraction concentration of 2,5-diphenyloxazole is 1%, and the mass fraction concentration of 1,4-bis(5-phenyl-2-oxazolyl)benzene is 0.02%.

6. The method for preparing a plastic optical fiber composite scintillator according to claim 1, characterized in that: In step 5), the heating temperature of liquid A is 65-80° C., and the insulation time is 45-50 hours; the speed of adding liquid A is 100 ml / h.

7. The method for preparing a plastic optical fiber composite scintillator according to claim 1, characterized in that: In step 6), the temperature rise and fall procedure after the A liquid is added is: First, raise the temperature in the sealed container to 100°C at a rate of 5°C per hour and maintain it for 120 hours. Then lower the temperature in the sealed container to room temperature at a rate of 5°C per hour.

Citation Information

Patent Citations

  • Organic / inorganic composite scintillator and preparation method thereof

    CN114085430A